Expressing Impoliteness in Political TV Debates - Žurauskaitė, Eglė (Lietuvių kalba, 2021)
This article examines impoliteness in political TV debates in Lithuania. Study adopts qualitative and quantitative content analysis method to analyze 720 minutes of political debates broadcasted before the 2016 Lithuanian Parliamentary elections. Current paper presents theoretical approach to impoliteness, which is later used in empirical analysis to address 2 main objectives: a) to study impoliteness in terms of directness/indirectness and b) to reveal how face threatening acts (FTAs) are expressed. The results of the study have revealed that impoliteness during political TV debates is almost equally expressed directly and indirectly. Direct impoliteness during political debates can be expressed using all functional types of the sentences. Indirect impoliteness in debates can be modified internally and externally using various language resources: inclusive we form, official addressing words, irony, parantheses. This suggests that impoliteness in the context of political TV debates is a unique phenomenon specified by various creative ways of using the language in order to publicly belittle political opponents.